Pengaruh Hedonic Shopping Motivation, Shopping Lifestyle, dan Sales Promotion Terhadap Impulse Buying pada E-Commerce Shopee - Lestari, Sri Katrina Bangnga; Ernawati, Maria Theresia; Pranatasari, Fransisca Desiana (Business Management Journal, 2023)
This study aims to determine: 1) the simultaneous effect of hedonic shopping motivation, shopping lifestyle, and sales promotion on impulsive buying, 2) the partial effect of hedonic shopping motivation on impulsive buying, 3) the partial effect of shopping lifestyle on impulsive buying, 4) the partial effect of sales promotion on impulse buying. This research was conducted in February 2023. The population in this study were users of the Shopee application, especially the students of Sanata Dharma University. Respondents in this study were 100 students with a sampling technique of purposive. The data analysis technique used in this research is multiple linear regression analysis, using SPSS 29.0 for windows application. The results of this study indicate that: 1) hedonic shopping motivation, shopping lifestyle, and sales promotion simultaneously affect impulsive buying, 2) hedonic shopping motivation partially affects impulsive buying, 3 shopping lifestyle partially affects impulsive buying , 4 ) sales promotion partially has no effect on impulse buying